Financial Management Model Village - Siswadi Sululing; Haruni Ode; Mohammad Gifari Sono (International Journal of Applied Business and International Management, 2018)
This research aims to improve knowledge of the village head and village apparatus about administering and accounting of financial transactions using accounting model village village, this type of research is the research field to the villages of recipients the village Fund, the allocation of funds, and local tax and regional levies in the Regency of Banggai Central Sulawesi Province. Sampling method was purposive sampling, while the analysis tools used are model villages, using accounting using public cash book, daily maid, cash book bank book, book, book inventory tax village, books supplies, books capital books, accounts receivable, and the book debts. Results of the study consist of APB Village consists of income of the village, which is a fund transfer from the Central Government, i.e. the village Fund, and the allocation of funds and village tax areas and regional retribution from the local government as well as financial assistance from the Government the counties and provinces,while shopping the village consists of the 56th Government field shopping village, shopping areas of implementation of the development of the village, shopping areas of civic construction, shopping areas, community empowerment and unexpected expenditures. Accounting model villages will produce financial laporaan village consisting of APB Village, reports, reports on the realization of the budget, the early village-owned wealth report, balance sheet and notes to financial statements.